2015
DOI: 10.7314/apjcp.2014.15.23.10393
|View full text |Cite
|
Sign up to set email alerts
|

The Polymorphism of Hypoxia-inducible Factor-1a Gene in Endometrial Cancer

Abstract: Background: Endometral carcinoma is the most common malignant tumor of the female genital tract and the fourth most common cancer in women after breast, colorectal and lung cancers Hypoxia-inducible factor -1 (HIF-1) is a key transcription factor that regulates cellular response to hypoxia HIF-1 plays important roles in the development and progression of cancer through activation of various genes that are involved in crucial aspects of cancer biology, including angiogenesis, energy metabolism, vasomotor functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…This finding can be explained by the fact that protein translation and proteasome-dependent degradation are impaired by hypoxia, which affects the HIF-1α levels (Anad et al, 2011). Furthermore, these results are in line with the previous findings indicating that mature and functional HIF-1α are generated by cells in response to hypoxia in solid tumors (Kafshdooz et al, 2014) which plays a pivotal role in tumor progression, infiltration and metastasis (Unwith et al, 2015). The results yielded by this study also demonstrated that serum HIF-1α was significantly correlated with ANGPTL4 serum and expression levels.…”
Section: Discussionsupporting
confidence: 92%
“…This finding can be explained by the fact that protein translation and proteasome-dependent degradation are impaired by hypoxia, which affects the HIF-1α levels (Anad et al, 2011). Furthermore, these results are in line with the previous findings indicating that mature and functional HIF-1α are generated by cells in response to hypoxia in solid tumors (Kafshdooz et al, 2014) which plays a pivotal role in tumor progression, infiltration and metastasis (Unwith et al, 2015). The results yielded by this study also demonstrated that serum HIF-1α was significantly correlated with ANGPTL4 serum and expression levels.…”
Section: Discussionsupporting
confidence: 92%
“…When the rate of tumor cell proliferation surpasses that of apoptosis, hypoxic foci begin to arise in the center of the growing tumor [131]. Hypoxiarelated centers of necrosis are among the most important inducers of angiogenesis at relatively early stages of cancer development through the production of the hypoxiainducible factor-1α (HIF-1α) [132]. Hypoxia-induced angiogenesis of the tumor, due to an increased release of HIF-1α, leads to a significant overexpression of VEGF, which usually increases the average microvascular density in the tissue [131,133].…”
Section: Hypoxia-inducible Factor 1 Dependent Cytokinesmentioning
confidence: 99%
“…HIF-1a is an oxygen stress factor that is highly expressed in hypoxia cells and has been increasingly recognized as playing a broad and critical role in normal development, postnatal physiology, cancer, and many other diseases ( 18 - 20 ). HIF-1a may be associated with EC based on the C1772T polymorphism ( 21 ). Horrée’s results showed that HIF-1a was not a risking factor for EC, although this study still maintains that HIF-1a promotes EC growth ( 22 ).…”
Section: Discussionmentioning
confidence: 99%